A Correlational Study on the Teaching Methodologies and the Competencies of Graduates in a Private University in the Philippines - Micabalo, Kingie; Poliquit, Winnie Marie; Ibanez, Estela; Pabillaran, Robert; Edicto, Quennie Marie; Cano, Jesszon (JPAIR Institutional Research, 2021)
Teaching and learning methodologies are significant factors in building students’ competency after college life, making them a good contender in the labor market. The study determined the impact of the varied methodologies in teaching and learning on the graduates' competency. The 181 graduate respondents participated in the survey on a snowball method in data gathering. Frequency and simple percentage, weighted mean, Chi-Square Test of Independence, and One-way ANOVA were used to treat and interpret the data. The findings revealed that, in a pervasive way, the teaching and learning methodologies among faculties embodied in the flipped classroom, project-based learning, cooperative learning, problem-based learning, and competency-based learning in the Department were perceived by the graduates. By this instance, further findings revealed a significant relationship with adopting these varied methodologies and its influence on the graduates' competency in oral/written communications, teamwork/ collaboration, information/ technology application, leadership, and professionalism/ work ethic. The study concluded that a more substantial imposition of teaching and learning methodologies to the students' could greatly emphasize graduates' professionalism, leadership, communication, collaboration, and knowledge in information technology. Furthermore, the influence of flipped classrooms, project-based learning, cooperative learning, problem-based learning, and competency-based learning in the teaching and learning experiences in the Department provides a good impact on their competency as a graduate. These practices indicate a strong alignment between the institution's interests which focuses on producing competent and innovative graduates that are efficient and effective in the labor market.
Keywords: Business and accountancy; teaching methodologies; competencies; non-experimental descriptive- correlational; Mandaue City; Philippines